SURVEI TINGKAT KESEGARAN JASMANI SISWA KELAS XII MIPA I MADRASAH ALIYAH NEGERI LANDAK - Nopi Mahendra (CV. Adiba Aisha Amira, 2023)
Physical fitness related to a student is an important aspect that must be maintained. To maintain physical fitness, students are required to be able to maintain their fitness by exercising regularly and getting sufficient quality and quantity of food. That way, students will have a high level of physical fitness and can use their thoughts and energy to be enthusiastic about activities at school. A good level of physical fitness is needed by every student. To find out whether a student's level of physical fitness meets the standards, a test needs to be carried out, namely using the Indonesian Physical Fitness Test (TKJI) method. The aim of this research was to determine the level of physical fitness of class XII MIPA 1 Madrasah Aliyah Negeri Landak Landak Regency students. The type of research used is survey research. The location of this research is Madrasah Aliyah Negeri Landak, Landak Regency. The population in this study was all 27 class XII MIPA 1 students. The sampling technique is to use cluster sampling. The sample in this research was 20 class XII MIPA 1 students.